The Impact of Television Advertising on Women in Nigeria and Iran - Egbai, Mary Julius (PREDESTINASI, 2019)
The impact of media on society is a widely discussed, debated and investigated subject of the 21st Century. The media are rightly considered as the fourth estate of a democracy. The media are also known as informal universities which provide constant education, orientation and guidance to the mankind. There is a phenomenal growth of mass media including television all over the globe. The role of television as a medium of communication and development is subjected to scientific research in Nigeria, Iran and elsewhere. A new generation of audience has grown up with television exposure in modern society. The impact of television advertising on the lives of women needs to be examined scientifically and systematically in developing countries like Nigeria and Iran. The present study evaluates the impact of television advertising on women in these two countries.